Investigating Safety Promotion Guidelines in Railway Construction Projects - Eshagh ARIANMEHR; Zahra SABZI; Faezeh ABBAS GOHARI; Mohsen ASGARI (بهداشت کار و ارتقای سلامت, 2022)
Introduction: Occupational accidents not only reduce social credibility and impose a heavy economic burden on the organization, but also cause fatalities and disability among personnel. This study aims to assess risk and review safety promotion guidelines in railway construction projects. Methods: This study investigated the safety status of Tehran-Karaj railway construction and increasing lines project in four phases, including infrastructure, technical buildings, superstructure, and joint activities. The data were gathered by reviewing project safety documentation, reported accidents, and risk assessment results by failure modes and effects analysis (FMEA) method. Risks were categorized based on control ability at three levels, including low, moderate, and high levels. Control measures were prioritized based on the risk coverage percentage, cost, implementation time, and effectiveness. Results: In total, 377 risks were identified, 19.9%, 61.2%, and 18.9% of which were in the low, moderate, and high levels, respectively. The most frequently identified risks and the highest rate of accidents were related to technical buildings (42.2%) and superstructure (36.6%) phases, respectively. In terms of consequence, the most severe accident occurred in the infrastructure phase within the contractors' scope of action. Falling from height was identified as the greatest threat against the project, and collapsing, falling, and hitting with materials as the key cause of the accident. It was found that controlling 39.8% of the risks could avert 73.3% of the project occupational accidents. Conclusion: The findings reveal the major role of senior management commitment to safety and emphasis on control measures, including implementing safety program training, increasing visits, and safety inspection, as well as implementing a permit to work system in all operational phases.